2016
DOI: 10.2147/ccid.s113044
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between severity of the local skin reactions and the rate of local skin reaction resolution in patients treated with ingenol mebutate gel

Abstract: BackgroundIngenol mebutate gel is a topical field treatment for actinic keratosis (AK). The treatment elicits application-site reactions in most patients. This analysis evaluated the relationship between the severity of reactions and the speed of their resolution.MethodsPatients in Phase III studies were treated for AKs on the face (n=218), scalp (n=56), and trunk and extremities (n=209). All of the patients were treated with either ingenol mebutate gel 0.015% once daily for three consecutive days (face/scalp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Due to its mechanism of action, the development of specific local skin responses (LSRs) such as erythema, ulcerations, and crusting (10) has been reported after the topical treatment with IMG. Evidence suggests that these LSRs tend to spontaneously resolve within 2-4 weeks after treatment, which is correlated with the initial severity shown within the affected skin field (11).…”
Section: Introductionmentioning
confidence: 81%
“…Due to its mechanism of action, the development of specific local skin responses (LSRs) such as erythema, ulcerations, and crusting (10) has been reported after the topical treatment with IMG. Evidence suggests that these LSRs tend to spontaneously resolve within 2-4 weeks after treatment, which is correlated with the initial severity shown within the affected skin field (11).…”
Section: Introductionmentioning
confidence: 81%
“…The prevalence of severe LSRs among various topical field treatment options is summarized in Table 1 [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28].…”
Section: Severe Local Site Reactions With Topical Field Treatment mentioning
confidence: 99%
“…Each of six LSR parameters—erythema, flaking/scaling, crusting, swelling, vesiculation/pustulation, and erosion/ulceration is graded from 0 to 4, giving a maximum composite score of 24 [15,29]. Jim On et al [16] reported data of two multicenter, randomized, parallel-group, double-blind, vehicle-controlled studies, involving face and scalp and classified patients with a composite score of 12 or higher as having a severe LSR. Thus, their reported prevalence of severe LSRs at day 4 was 24.5%.…”
Section: Severe Local Site Reactions With Topical Field Treatment mentioning
confidence: 99%